BLOOD PLASMA TRACE ELEMENTS IN REPEAT BREEDING MEHSANA BUFFALOES - KAPADIYA, F M; SIDDIQUEE, G M (The Indian Journal of Animal Reproduction, 2023)
Blood plasma trace minerals analysis indicated that the levels of iron, copper, cobalt, zinc and manganese were comparatively higher in antibiotics (Cephalexin or Ciprofloxacin+ Tinidazole) treated Groups-I and II as compared to untreated control Group of repeat breeding buffaloes (n=6 each) whereas cobalt and manganese were significantly higher in treated Groups-I.